ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN ARSIP BERBASIS WEB PADA SEKOLAH TINGGI ILMU TARBIYAH ( STIT ) KABUPATEN TEBO - Amin, Sukron; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2018)
In the processing of archiving documents study program at the Sekolah Tinggi Ilmu Tarbiyah (STIT) Tebo, special in compile each one document to the bookself, still using manually sistem and for lecturers who borrowed the documents study programs have to come down and look for the documents to Kaprodi, and its make a system running slow , so the search for documents may be less than the maximum. That why to solved its we need a system that can archive. The document to be more courses either in the form of web. The information system will be designed with the Prototype method and system modeling using object-oriented modeling that use case diagrams, activity diagrams, and class diagrams. The results of this research is to design a prototype system of Web-Based Records Management information At Sekolah Tinggi Ilmu Tarbiyah (STIT) Tebo. With this information system can minimize the problem and is expected to make it better and faster in the archiving of documents.